Marketing Strategy in Moderation of Social Media & Marketplace to Increase Sales Turnover Anticipating the Impact of the Covid-19 Pandemic at Rasana Juice Surabaya - Anggreani, Kamellia Nety; Alimudin, Arasy (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to determine the effect of marketing strategy on sales turnover with each moderating variable, namely social media and marketplace. Design/Methodology/Approach: This research is a causal associative research with a quantitative approach, for data processing with SEM method and using SmartPLS 3.0 software. The variables analyzed in this study are product (X1) , price (X2) , location/distribution (X3) , promotion (X4) , sales volume (Y) , social media (SM) and marketplace (M). The population in this study is MSMEs for beverage products with a total sample of 152 MSMEs. The data collection methods used were interviews and questionnaires with a Likert measurement scale, then the questionnaire was tested by T-test (partial) and F-test (simultaneous). Findings: The results of testing the X variable against Y with social media moderator show that all variables have a significant and positive effect except the price variable on sales volume in social media moderation (X2*SM -> Y) and promotion variables on sales volume in social media moderation (X4*SM -> Y) , both results were rejected because P Value > 0.05. While the research results from testing the X variable against Y with the marketplace moderator show that all variables have a significant and positive effect except the product variable on sales volume (X1 -> Y) and the price variable on sales volume in marketplace moderation (X2*M -> Y) , both results > 0.05 which means it is not significant. Paper type: Research paper